"Notatki do gwałtu" (opatrzone wstępem i komentarzem Piotra Sobolczyka) - Morska, Izabela; Sobolczyk, Piotr (Zagadnienia Rodzajów Literackich, 2024)
Notes on Rape is a tripartite presentation of a literary document from 1985. The main section of the presentation consists of fragments from one of Izabela Morska’s notebooks with notes from an MA thesis. This particular selection from a notebook numbers 49 pages. Morska is one of Poland’s leading feminist and queer writers. Her dissertation’s topic was Death as Rape in the Poetry of Stanisław Grochowiak and she defended it in 1986. These notes blend Morska’s own thoughts on the philosophy of rape which derives from de Sade’s ideas filtered as noteworthy by Rene Girard, her major inspiration at that time, with quotations from the articles she read, and with her own poems. Her handwriting was rewritten by Piotr Sobolczyk who also wrote an introductory editor’s comment and the third section of the presentation, i.e. a few remarks on Morska’s philosophy of rape. In this section Sobolczyk positions Morska’s original attempt among historical debates on feminism (second-wave feminism and its sex wars) and among current debates on the “culture of rape” and trauma. It is worth noting that none of these contexts were known back then by Morska and that makes her approach even more original. Morska defines rape quite broadly and metaphisically, as nature’s drive, force of movement. In the context of current debates such widening of the meaning might be perceived as disregardful of corporal suffering; however, Sobolczyk inscribes this problem into the frame of a larger discussion on the limits of metaphor, exemplified famously by Martha Nussbaum’s criticism of Judith Butler.